An overview of Personalized Medicine landscape and policies in the European Union. (28th October 2022) - Beccia, F; Hoxhaj, I; Castagna, C; Strohäker, T; Cadeddu, C; Ricciardi, Walter; Boccia, S
Abstract: Background: The spread of Personalized Medicine (PM) over the last decade defined a revolution in healthcare systems. PM is among the priorities of the European Commission's research agenda, which funded the IC2PerMed international project aiming to integrate China into the International Consortium of PM (ICPerMed). In the context of this project, we mapped the existing policies related to PM in the European Union (EU) and at the EU Member States (EU-MS) level. Methods: PubMed, Google Scholar, Google, Microsoft and national and international institutions' official repositories were searched in order to identify documents on PM-related policies, programmes and action plans at the EU and EU-MS level, published up to December 2020. Results: We identified 28 policies in the EU aimed at improving public health promoting and fostering PM implementation, through some actions including the standardization of good medical practice, use of big data and digital innovation, data sharing and cross-border interoperability, healthcare sustainability, disease prevention and patients'/citizens' engagement. We identified 23 policies at EU-MS level which, notwithstanding national differences, have a common focus, such as patient-tailored treatment and targeted prevention, education of healthcare workers, research and innovation, big data harmonization and healthcare system sustainability. Conclusions: The definition of an integrated regulatory framework is essential to turn PM into an opportunity for citizens and patients with the involvement of all the stakeholders. This work can provide a valuable tool for decision-makers to define common approaches, priorities for research, development and increase international collaboration, which could overcome the fragmented European scenario and align the future direction on PM.